Tinjauan Kuat Lentur Pelat Beton Geopolymer Dengan Tulangan Bilah Bambu Yang Dirangkai Dan Di Perkuat Kawat Galvanis Menyilang - Rahabistara, Frenda; , Ir. Aliem Sudjatmiko, M.T; , Basuki, S.T, M.T (2016)
Geopolymer is an environmentally friendly material that is commonly developed as an alternative to cement concrete in the future. Because the material is composed of natural materials synthesis non organic through polymerization. The main ingredients of geopolymer concrete production, is a material that contains silicon and aluminum. These elements, of which there are many in the industry byproduct waste material, such as fly ash ( fly ash ) coal combustion. To dissolve the elements silicon and aluminum, as well as enabling the occurrence of chemical reactions, use a solution of alkali. At the same time the need to use the main reinforced concrete reinforcing steel also increased. Increased need for steel reinforcement will lead to price rises so that it becomes expensive and scarce. As for alternatives that can be used as a substitute for concrete reinforcing one of them is bamboo. specific advantages in bamboo that bamboo fiber has a high tensile strength. Alkaline activator used in this study a Na2SiO3 ( sodium silicate ) and NaOH ( sodium hydroxide ) concentration of 8M. Variations aggregate and binder ( fly ash and the activator ) = 80 % : 20 %, and the ratio of activator Na2SiO3 : NaOH = 4 : 2. Bamboo is used in the form of bamboo ori strung together. Geopolymer concrete treatment methods in a way allowed to stand at room temperature, whereas normal concrete by soaking in water. Tests done when the concrete was only 28 days. For this research, testing concrete compressive strength geopolymer normal and cylindrical with f'c respectively 19.919 MPa and 12.864 MPa. The size of the bamboo used is 2 cm wide and 0.8 cm high, sized galvanized wire Ø 1.02 mm and Ø 1.29 mm, and a concrete slab measuring 60 cm x 60 cm x 8 cm. Research results obtained, that is maximum bending moment of normal concrete plate steel reinforcement and steel reinforcement geopolymer respectively 3.514 kN.m and 1.994 kN.m, maximum bending moment and the normal concrete plate of reinforced geopolymer bamboo assembled at 3.295 kN.m and 1.751 kN.m, maximum bending moment and the normal concrete plate of reinforced geopolymer bamboo assembled together with galvanized wire Ø 1.02 mm by 3.369 kN.m and 1.825 kN.m, and maximum bending moment and the normal concrete plate of reinforced geopolymer bamboo assembled together with galvanized wire Ø 1.29 mm by 3.372 and 1.885 kN.m kN.m. From the results of this comparison shows the flexural strength of normal concrete is still higher than it geopolymer concrete could be due to a mixture of binders activators are not optimal